1997
DOI: 10.1177/039139889702000708
|View full text |Cite
|
Sign up to set email alerts
|

External Biodegradable Supporting Conduit Protects Endothelium in Vein Graft in Arterial Interposition

Abstract: The prevention of circumferential distension could reduce structural damage in arteriovenous grafts. We studied the effect of an external biodegradable supporting conduit on the endothelium and extracellular matrix in vein graft in a pig model. Cephalic vein control grafts (Group I) and jugular veins wrapped in a vicryl mesh tube (I.D. 4 mm) (Group II) were implanted into autologous carotid arteries (n = 14). The grafts were explanted after 1 and 24 hours and at 1 and 3 weeks and evaluated by ELISA for endothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…Numerous reports indicate that thickening happens during the remodeling process in grafts both with and without protection [13,15]. This study showed consistent results (see Figure 5); the wall of the grafts was much thicker than that of the vein (there was a significant statistical difference between HV and HSM/HM).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Numerous reports indicate that thickening happens during the remodeling process in grafts both with and without protection [13,15]. This study showed consistent results (see Figure 5); the wall of the grafts was much thicker than that of the vein (there was a significant statistical difference between HV and HSM/HM).…”
Section: Resultssupporting
confidence: 86%
“…It has been shown that this protection could preserve the endothelium cells (ECs), smooth muscle cells (SMCs) and elastic fibers and increase vasa vasorum [12,13]. It also indicates that the ES can decrease wall thickness and matrix deposition significantly [13-15], prevent atherosclerosis around the anastomosis [16-20] even in hypercholesterolemic animals [15], and reduce cell apoptosis [3,7,21,22]. Moreover, ES can not only improve the patency of the normal vein graft, but also means that varicose and dilated veins can be used [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…This has been described previously in a pig vein graft model in which an external biodegradable supporting conduit protected the endothelium in vein grafts. 26 In unstented vein grafts, SMC loss was observed during the first week after surgery. This is in accordance with SMC loss described in specimens of early vein graft in patients 10 and in various experimental studies.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, many procedures have been adopted to reduce neointima formation through lowering the wall tension of veins. It has been established that a bioabsorbable, nonrestrictive, external sheath could inhibit vein graft thickening in animal and human experiments [3,11]. However, these external stents have the risk of injury to the vein wall and might be limited by side to side anastomoses.…”
Section: Discussionmentioning
confidence: 99%